Revolutionizing construction safety: introducing a cutting-edge virtual reality interactive system for training US construction workers to mitigate fall hazards - Alzarrad, Ammar; Miller, Matthew; Durham, Luke; Chowdhury, Sudipta (Frontiers in Built Environment, 2024)
The construction industry is fraught with hazards, chief among them being the risk of falls from elevated positions, which are a leading cause of both fatalities and injuries among workers. Despite the prevalence of traditional safety training methods, their effectiveness in reducing fall risks remains limited. To solve this issue, this study proposes the adoption of interactive VR technologies to provide construction workers with immersive training experiences in the critical domain of fall safety. This approach not only ensures adherence to the Occupational Safety and Health Administration (OSHA) requirements but also leverages VR’s immersive capabilities to create a comprehensive and effective learning tool. To evaluate the proposed system’s efficacy, the researchers conducted an empirical assessment involving eighty-two construction workers from two small enterprises. Participants were divided into two groups: one receiving traditional training and the other undergoing VR-based instruction. Both groups underwent pre- and post-training evaluations comprising six targeted questions designed to measure the impact of each training method on their understanding and awareness of fall safety practices. The comparative analysis revealed no significant differences in baseline knowledge between the two groups prior to the training interventions. However, post-training evaluations demonstrated a notable improvement in the VR group, with a significant decrease in the number of incorrect responses, in stark contrast to the group subjected to traditional training methods. Statistical analysis further confirmed the superiority of VR training in enhancing participants’ knowledge. This was quantified by a p-value of 0.0016, indicating a high level of statistical significance well below the conventional threshold of 0.05. This study highlights the significant advantages of VR technology in construction safety training, demonstrating its superiority over traditional training methods in terms of knowledge retention and practical application. The results strongly support the wider adoption of VR in safety training, indicating its potential to enhance safety outcomes in the construction sector.